Normative Political Communities: Foundations for a Hartian Theory of State and Non-State Law - Fabra-Zamora, Jorge L. (My University, 2019)
This dissertation outlines a theory of law capable of explaining both the legal systems of domestic states and other types of legal phenomena different from state law that I will call non-state legal phenomena. Central examples of non-state law include indigenous and customary laws, the international legal order, the European Union, and transnational commercial law. This theoretical framework aims to formulate and resolve questions about the common features shared by different types of legality and the distinctive legal character of non-state legal phenomena. It also sets the stage for doctrinal and politico-moral inquiries about these phenomena. My account draws liberally from central themes of HLA Hart’s theory of state law that I deem applicable outside the domestic context. One key idea is the notion of normative order or unified complexes of interrelated rules that regulate specific domains of action. The refined Hartian view that I develop here distinguishes between two kinds of normative orders, sets and systems, which differ in their characteristic features and that allow for different doctrinal and moral inquiries. While these tools can be used to explain both state and non-state normative phenomena, I shall consider as law the normative orders of political communities, i.e. groups whose participants efficaciously employ intense forms of social pressure to secure conformity to norms that regulate pressing politico-moral issues. With these elements in place, the legal domain can be characterized as a constellation of sets and systems that constitute political communities at the state, non-domestic, international, supra-national, and potentially global levels. The argument proceeds as follows. Chapter 1 sets the stage of this inquiry. Chapter 2 explicates the key insights of the Hartian framework. Chapter 3 defends the applicability of this framework to non-state contexts. Chapter 4 illustrates its explanatory virtues by applying it to two regimes of international trade law. The conclusion summarizes the central insights of this view and highlights the avenues for future research.
Keywords: legal philosophy; HLA Hart; non-state law; legal pluralism; authority; international law; WTO; legal officials; normative order; rule of recognition